2019
DOI: 10.1093/jxb/erz325
|View full text |Cite
|
Sign up to set email alerts
|

Autopolyploidization in switchgrass alters phenotype and flowering time via epigenetic and transcription regulation

Abstract: Polyploidization is a significant source of genomic and organism diversification during plant evolution, and leads to substantial alterations in plant phenotypes and natural fitness. To help understand the phenotypic and molecular impacts of autopolyploidization, we conducted epigenetic and full-transcriptomic analyses of a synthesized autopolyploid accession of switchgrass (Panicum virgatum) in order to interpret the molecular and phenotypic changes. We found that mCHH levels were decreased in both genic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 93 publications
3
19
0
Order By: Relevance
“…In this study, we use 8X Alamo and 4X Alamo to process the drought treatment at various time points, followed by physiological and transcriptional analyses. Our previous study found that the sequence of 8X and 4X Alamo switchgrass were 99% identical with each other [52]. The analyses of this study could provide insights about drought the mechanism of response in switchgrass at both physiological and transcriptional levels before/after WGD and also provide abundant data for the drought tolerant breeding of switchgrass.…”
mentioning
confidence: 60%
“…In this study, we use 8X Alamo and 4X Alamo to process the drought treatment at various time points, followed by physiological and transcriptional analyses. Our previous study found that the sequence of 8X and 4X Alamo switchgrass were 99% identical with each other [52]. The analyses of this study could provide insights about drought the mechanism of response in switchgrass at both physiological and transcriptional levels before/after WGD and also provide abundant data for the drought tolerant breeding of switchgrass.…”
mentioning
confidence: 60%
“…Considering that phenotype changes due to polyploidy in isogenic individuals cannot be related to sequence-based regulatory differences, DNA methylation level differences might be implicated. Studies identifying differentially methylated regions (DMRs) in diploids and autopolyploids of Arabidopsis, rice and switchgrass support this idea (Yan et al, 2019;Yu et al, 2010;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Newly created autopolyploids can contain epigenetic modifications, e.g. switchgrass [53] and Arabidopsis [54], but effects on gene expression are much smaller than in allopolyploids [55] and occur rather stochastically [56].…”
Section: Discussionmentioning
confidence: 99%